2006
DOI: 10.1532/ijh97.06009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Polycythemia Vera and Essential Thrombocythemia in Japan: Retrospective Analysis of a Nationwide Survey by the Japanese Elderly Leukemia and Lymphoma Study Group

Abstract: We conducted the first nationwide survey to clarify the clinical features, treatment methods, and prognoses for polycythemia vera (PV) and essential thrombocythemia (ET). A 1-page questionnaire was mailed to members of the Japanese Elderly Leukemia and Lymphoma Study Group (JELLSG). Surveys on 647 patients (PV, 266 patients; ET, 381 patients) were returned and analyzed. Thrombotic events at diagnosis and during follow-up occurred at rates of 15.4% and 8.5%, respectively, in PV cases and 17.6% and 8.7% in ET ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…40 Concerning the potential role of cytotoxic agents in the development of leukemia, prior studies reported that hydroxy-urea may be leukemogenic, 19,41 and that the use of more than one cytotoxic agent may increase the risk of leukemic transformation. 4,42 However, leukemia may develop in patients who have never received cytotoxic drugs, 43 and large studies did not show that cytotoxic agents were involved in leukemic transformation. [3][4][5] Our results indicate that the risk of leukemia increases over time and that patients treated with cytotoxic agents do not have a significantly different risk of leukemic transformation compared to that of patients receiving antiplatelet agents alone.…”
Section: Discussionmentioning
confidence: 99%
“…40 Concerning the potential role of cytotoxic agents in the development of leukemia, prior studies reported that hydroxy-urea may be leukemogenic, 19,41 and that the use of more than one cytotoxic agent may increase the risk of leukemic transformation. 4,42 However, leukemia may develop in patients who have never received cytotoxic drugs, 43 and large studies did not show that cytotoxic agents were involved in leukemic transformation. [3][4][5] Our results indicate that the risk of leukemia increases over time and that patients treated with cytotoxic agents do not have a significantly different risk of leukemic transformation compared to that of patients receiving antiplatelet agents alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxycarbamide (HC) is the most widely used CRT for ET in Japan [4]. It has been suggested that long-term HC use is associated with a higher incidence of secondary leukemia [5].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In contrast to this scenario regarding thrombosis in ET, the pertinent literature reveals a considerable degree of inconsistency regarding life expectancy and the incidence of LT and its relationship to drug therapy. 1,[9][10][11][12][13][14][15][16][17][18][19] One major factor that contributes to the discrepancy in reported figures concerning survival and LT in ET is the small number of events and their dependence on time that necessitates both large sample size and long-term follow-up. Another factor that is often overlooked is the possibility of interstudy differences in risk distribution of the study population that arise from diagnostic imprecision and referral bias, 20,21 among other things.…”
Section: Introductionmentioning
confidence: 99%